ANALISIS KUALITAS DAGING AYAM BROILER ASAL PASAR SWALAYAN DAN PASAR TRADISIONAL DI KOTA MEDAN SUMATERA UTARA - Dhirgo Adji; Angelina Susanty; Ma’ruf Tafsin (Jurnal Sain Veteriner, 2021)
The mean protein content in broiler chickens from high to low were respectively protein in breast meat from supermarkets: 16.83 ± 0.42 %; breasts from the traditional market: 15.63 ± 1.09 %, thighs from the supermarket: 14.5 ± 0.57 % and thighs from the traditional market: 13.6 ± 0.38 gr / 100 %. Based on all of the datas collection,  the result of statistical analysis using a 2x2 factorial pattern showed that there were no significant differences of water content (P>0.05) whreas: the ash, carbohydrates, fats and proteins showed significant (P£0.05).Thighs from traditional markets 4.5 ± 0.60 % and chest from traditional markets from 5.3 ± 0.69 %. The Average of fat content of broiler meat in the thigh, from supermarket: 2.56 ± 0.63 %; chest origin supermarket 1.2 ± 0.5 %; thigh meat from traditional markets: 3.15 ± 0.21 % and breast meat from traditional markets: 1.8 ± 0.227 %. Broiller is one of the biggest contributor to animals protein from livestock and is a superior commodity in Indonesia. At present, the broiler chicken industry has developed rapidly and become the largest contributor to animal protein as well as a major source of consumer menus that are very easy to obtain, both in modern and traditional markets. After the achievement of the population of broiller chickens, government policy began to emphasize on improving the quality of meat by changing meat characteristics such as appearance, texture, moisture content, firmness, softness, odor, taste and the nutritional content is no exception. Thirty-two samples of broiller chicken meat consisting of 16 meat samples purchased from 4 supermarkets and 16 samples purchased from 4 traditional markets were used as research objects. A hundred grams of fresh meat per sample were purchased and immediately packed in aluminum foil, packaged in a cooler box then sent to the Food and Nutrition Laboratory, Inter-University Center, Gadjah Mada University for proximate analysis. The results of the examination of water concentration showed that the average of water content of thigh meat from supermarkets was 76.26 ± 0.86 %; supermarket breast meat 74.135 ± 0.92 %; thigh meat from the traditional market 75 ± 0.56 % and breast meat from the traditional market: 75.64 ± 1.044 %. Analysis of the average levels of the ash concentration respectively: thighs from the supermarket 0.96 ± 0.027 %, chest from the supermarket 1.095 ± 0.05 %, thighs from the traditional market 1.034 ± 0.106 % and breasts from the traditional market 1.155 ± 0.11%. The average of carbohydrate levels were consecutive: Thigh meat from the supermarket: 5.6 ± 1.33 %; chest of origin of the supermarket: 6.7 ± 1.078 %;